The Effect of Using tow Methods of Pronounced and written Feed Back in Academic acquisition of students of technical medicine institute in philosophy curriculum (Journal of the College of Education for Women, 2019)
The world faces, in the last years of the last century and the beginningof the current century i.e. the 21st century, a great expansion and a largeopenness on new worlds in studies differ in their development, detection ofthinking methods and practice of mental processes.The recent studies have proved an increase in the scientificachievement among students through the presence of new techniques one ofwhich is Landa Organizing and Exploring Model concerning Physiology thatdeals with various body organs.This research aims at identifying the effectiveness of Landa Model onthe achievement of the Technical Medicine Institute students in Physiology soas to be sure of the following nil hypothesis: there is no statistically significantdifference at the level (0.05) between the mean scores of the experimentalgroup studying physiology according to Landa Model and the mean scores ofthe control group studying the same material according to the normal method.The experimental design with the partial control was used. The currentresearch was confined with the students of the Technical Medicine Institute forthe academic year 2006-2007 where section (A) and (B) were chosenrandomly. The sample number mounted (70) male and female students, (35)male and female students for each section. The (age, previous studyachievement of Biology and intelligence) variables were equalized. The facialvalidity, content validity, difficulty level, alternative effectiveness and itemdiscrimination were checked out according to reliability coefficient by usingPearson equation recording (85%) for the items subjected to the test.The results showed the superiority of the experimental group whostudied physiology according to Landa Model on the control group whostudied physiology according to the normal method. It was concluded thatusing Landa Model in teaching Physiology resulted in increasing the students'achievement. The researcher recommended using Landa Model in teachingand suggested conducting more studies in other items to identify their effectextent on study achievement.